Status and function of betaDadrenoreceptors and their modification during betaDblocker treatment in patients with arterial hypertension and chronic heart failure - O. A. Maneshina; M. V. Leonova; Yu. B. Belousov (Российский кардиологический журнал)
Despite modern pharmacology's advances in developing new medication forms, some patients still are therapy-resistant. This review is devoted to beta-adrenoreceptor status, function, and modification during beta-adrenoblocker treatment in patients with arterial hypertension and chronic heart failure. Possible causes of beta-blocker resistance are described, including receptor-medication interaction, and beta-adrenoreceptor polymorphism.